PENGARUH TARI RENTAK BULIAN TERHADAP KEMAMPUAN MOTORIK KASAR PADA ANAK USIA 5-6 TAHUN DI TK ZAMRAD KECAMATAN TENAYAN RAYA PEKANBARU - Afliza, Helsi; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to find out the influence of rentak bulian dance against gross motor skill in children aged 5-6 years in TK Zamrad Tenayan Raya District Pekanbaru. This research used experimental method with one group pre-test post-test design. The sample which is used in this research is 18 children in TK Zamrad The data Collection technique used in this research is observation. While the data analysis technique used in this study using T-test analysis. In this hypothesis test of this research, there is an influence of rentak bulian dance against gross motor skill in children aged 5-6 years in TK Zamrad. The result of tcalculated is about = 18,495 > ttable = 2,110 with sig 0,000, because the sig <0,05. It can be concluded that there is an influence of rentak bulian dance against gross motor skill in children aged 5-6 years in TK Zamrad Tenayan Raya District Pekanbaru which is significant as big as 59,59%. Keywords: Gross Motor Skill, Rentak Bulian Dance